Situation and prospects of treatment technologies for mine water containing ammonia nitrogen - LI Fuqin*; WANG Cong; ZHENG Jiongzhou; CHEN Yuhang; ZHOU Rulu (能源环境保护)
As the discharge standards for mine water treatment become more stringent, the requirements for effective removal of ammonia nitrogen from mine water are strongly needed. While there are several methods available for treating ammonia nitrogen in wastewater, there is relative scarcity of literature addressing the treatment of mine water specifically containing ammonia nitrogen. To address this issue, this paper conducted a comprehensive analysis of the sources and characteristics of ammonia nitrogen in mine water. It also reviewed various primary technologies used for treating low concentrations of ammonia nitrogen in wastewater, including ion exchange, adsorption, oxidation, membrane separation, and biological methods. The paper aimed to provide technical support for the treatment of ammonia nitrogen-containing mine water in China. The findings of the study reveal that ammonia nitrogen in mine water primarily originates from three sources: Naturally high ammonia nitrogen content in groundwater, the usage of emulsion, dust suppressants, grouting, and gelling materials in the underground coal production process, and the lateral recharge from polluted surface water containing ammonia nitrogen. Ammonia nitrogen-containing mine water is characterized by relatively low ammonia nitrogen content (generally <5 mg/L), neutral or slightly alkaline pH, and generally low chemical oxygen demand (COD) levels. In order to control the generation of ammonia nitrogen at its source, it is recommended to minimize the use of raw materials containing nitrogen in coal mining production processes. Additionally, it is advised to collect, treat and manage production waste liquids and excreta. For mine water with low concentrations of ammonia nitrogen (<2 mg/L), oxidation is considered a more reasonable treatment choice. On the other hand, for mine water with higher ammonia nitrogen content, biological treatment is a cost-effective approach. Considering the varying water quality characteristics of mine water with different concentrations of ammonia nitrogen, future development trends should focus on the research and development of corresponding chemical oxidation and biological treatment technologies.